Georgia Architectural and Historic Properties Survey of Quitman (rural) [300] One mile north of Quitman, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman (rural) [300] One mile north of Quitman, Valdosta, Ga. December 1980. Georgian plan house, rectangular plan. Hipped and gabled roof. Hipped portico. Clapboard siding. Sash windows with 2/2 lights (shutters). Set on brick piers. Good condition. Date of Construction: c. 1900. Typical Georgian plan house, common to the Brooks County area.
Georgian plan house, rectangular plan. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 716 KB (734,051 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)